Utilization of Coconut Husk Waste (Cocos Nucifera Linn) as an Environmentally Friendly Disinfectant Material for The Prevention of COVID-19 - Abdurrahman Fardiaz, Muhammad; Ari Rifqi, Muhammad (Rifa'Institute, 2022)
Introduction: In the midst of the outbreak of the spread of COVID-19 which is currently increasing, people are actively taking precautions, one of which is by sterilizing using disinfectants. But a problem arises among the people that mass spraying of disinfectants gives rise to environmental pollution. This is because the ingredients for making disinfectants come from chemicals that tend to be non-biodegradable by soil, plants, and microorganisms. Objective: The purpose of this study is to help the community to solve this problem by making environmentally friendly disinfectants from coconut husk waste materials. Method: In this study, the method used is a quantitative approach because this research is presented using aspects of measurement, concentration calculation, and certainty of numerical data Results and Discussion: A sap liquid is proven to have many benefits, namely as a biopesticide, insecticide, disinfectant, and preservative. The liquid smoke production process is also classified as environmentally friendly because all residues can be reused or zero waste. Based on the data obtained, the percentage of liquid smoke of 1.6% has a better ability to inhibit the growth of microorganisms than the percentage of liquid smoke of 0.4% and 0.8%. Conclusion: With this disinfectant, it is hoped that it can reduce the risk of environmental pollution, can effectively sterilize in the community environment for the prevention of COVID-19, and can reduce coconut husk waste